In vitro vascular toxicity of tariquidar, a potential tool for in vivo PET studies. (October 2017) - Durante, Miriam; Frosini, Maria; Fusi, Fabio; Neri, Annalisa; Sticozzi, Claudia; Saponara, Simona
Abstract: The P-glicoprotein (P-gp) inhibitor tariquidar is used to detect functional alterations of blood brain barrier pumps in PET imaging. The doses required, however, up to 4-fold higher than those already used in clinical trials to reverse multidrug resistance, cause syncopal episode and hypotension. Therefore, the effects of these doses toward the vasculature were investigated and an in-depth analysis of tariquidar-mediated effects on A7r5 and EA.hy926 cells viability, on the mechanical activity of freshly and cultured rat aorta rings and on L-type Ca 2+ current [ICa(L) ] of A7r5 cells has been performed. In both A7r5 and EA.hy926 cells, tariquidar was not cytotoxic up to 1 μM concentration. On the contrary, at 10 μM, it caused apoptosis already after 24 h treatment. In fresh aorta rings, 10 μM tariquidar partially relaxed phenylephrine-, but not 60 mM K + (K60)-induced contraction. In rings treated with 10 μM tariquidar for 7 days, the contractile response to both phenylephrine and K60 remained unchanged. Finally, tariquidar did not modify ICa1.2 intensity and kinetics. In conclusion, Tariquidar might exert both cytotoxic and acute, weak vascular effects at concentrations comparable to those employed in PET imaging. This implies that caution should be exercised when using it as diagnostic tool. Highlights: Tariquidar is usually used to detect functional changes of BBB pumps in PET imaging. The doses injected have caused occasional syncopal episode and hypotension. The effects of these doses toward the vasculature were thus investigated in vitro. Tariquidar might exert both cytotoxic and acute, weak vascular effects. More caution should be so exercised when using it as diagnostic tool in patients.